Oscillatory shear stress promotes vein graft intimal hyperplasia via NADPH oxidase-related pathways - Yao, Guoqing; Li, Huanhuan; Zuo, Xiangyi; Wang, Chunkai; Xiao, Yelei; Zhao, Yu; Wang, Xuehu (Frontiers in Surgery, 2023)
Background: Uncontrolled endothelial overproliferation after autologous saphenous vein grafting triggers a high restenosis rate; however, its association with the activation of NADPH oxidase (NOX)-related pathways is unclear. Here, we investigated the effects and mechanism of oscillatory shear stress (OSS) on grafted vein intimal hyperplasia. Methods: Thirty male New Zealand rabbits were randomly divided into control, high-OSS (HOSS), and low-OSS (LOSS) groups, and the vein grafts were freed after 4 weeks. Hematoxylin and eosin staining and Masson staining assays were used to observe morphological and structural changes. Immunohistochemical staining was used to detect α-SMA, PCNA, MMP-2, and MMP-9 expression. Immunofluorescence staining was used to observe reactive oxygen species (ROS) production in the tissues. Western blotting was used to determine the expression levels of pathway-related proteins (NOX1, NOX2, AKT, p-AKT, and BIRC5), PCNA, BCL-2, BAX, and caspase-3/cleaved caspase-3 in tissues. Results: Blood flow velocity was lower in the LOSS group than in the HOSS group, while vessel diameter did not change significantly. Shear rate was elevated in both HOSS and LOSS groups but was higher in the HOSS group. Additionally, vessel diameter increased with time in the HOSS and LOSS groups, whereas flow velocity did not. Intimal hyperplasia was significantly lower in the LOSS group than in the HOSS group. Endothelial hyperplasia was dominated by smooth muscle fibers in the grafted veins and collagen fibers in the mesothelium. OSS restriction significantly reduced the α-SMA, PCNA, MMP-2, and MMP-9 levels. Moreover, ROS production and the expression of NOX1, NOX2, p-AKT, BIRC5, PCNA, BCL-2, BAX, and cleaved caspase-3 were phase-reduced in LOSS compared to the levels in the HOSS group. Total AKT was not differentially expressed among the three groups. Conclusion: OSS promotes the proliferation, migration, and anti-apoptosis of subendothelial vascular smooth muscle cells in grafted veins, which may be related to the regulation of downstream p-AKT/BIRC5 levels through the increased production of ROS by NOX. Drugs inhibiting this pathway might be used to prolong vein graft survival time.